The architecture of Fazang's six characteristics. - Jones, Nicholaos (British Journal for the History of Philosophy, 2019)
This paper examines the Huayan teaching of the six characteristics as presented in the Rafter Dialogue from Fazang's Treatise on the Five Teachings. The goal is to make the teaching accessible to those with minimal training in Buddhist philosophy, and especially for those who aim to engage with the extensive question-and-answer section of the Rafter Dialogue. The method for achieving this goal is threefold: first, contextualizing Fazang's account of the characteristics with earlier Buddhist attempts to theorize the relationships between wholes and their parts; second, explicating the meaning Fazang likely attributes to each of the six characteristics; third, situating the characteristics as explicated within Fazang's broader metaphysical framework.